Data integration: “Seamless data harmony: The art and science of effective data integration” - Saloni Kumari (International Journal of Engineering and Technology, 2023)
The idea of data integration has evolved as a key strategy in today's data-driven environment, as data is supplied from various and heterogeneous sources. This article explores the relevance, methodology, difficulties, and transformative possibilities of data integration, delving into its multidimensional world. Data integration serves as the cornerstone for well-informed decision-making by connecting heterogeneous datasets and fostering unified insights. This article gives readers a sneak preview of the in-depth investigation into data integration, illuminating its technical complexities and strategic ramifications for companies and organizations looking to maximize the value of their data as-sets.